Identification of aberrantly expressed lncRNAs and ceRNA networks in multiple myeloma: a combined high-throughput sequencing and microarray analysis - Lu, Min-Qiu; He, Yu-Qin; Wu, Yin; Zhou, Hui-Xing; Jian, Yuan; Gao, Wen; Bao, Li; Chen, Wen-Ming (Frontiers in Oncology, 2023)
Background: This study aimed to explore the potential effects of long noncoding RNAs in MM（multiple myeloma） patients using two detection methods: high-throughput sequencing and microarray. Methods: In this study, lncRNAs were detected in 20 newly diagnosed MM patients, with 10 patients analyzed by whole-transcriptome-specific RNA sequencing and 10 patients analyzed by microarray (Affymetrix Human Clariom D). The expression levels of lncRNAs, microRNAs, and mRNAs were analyzed, and the differentially expressed lncRNAs identified by both methods were selected. The significant differentially expressed lncRNAs were further validated using PCR Results: This study established the aberrant expression of certain lncRNAs involved in the occurrence of MM, with AC007278.2 and FAM157C showing the most significant differences. The top 5 common pathways identified by KEGG analysis were the chemokine signaling pathway, inflammatory mediator regulation, Th17 cell differentiation, apoptosis, and NF-kappa B signaling pathway. Furthermore, three miRNAs (miR-4772-3p, miR-617, and miR-618) were found to constitute competing endogenous RNA networks (ceRNAs) in both sequencing and microarray analyses. Conclusions: By the combination analysis, our understanding of lncRNAs in MM will be increased significantly. More overlap diffirent expressed lncRNAs were found to predict therapeutic targets precisely